I Want Your Sext: Sexting and Sexual Risk in Emerging Adult Minority Men. - Davis, Mikaela Jessica; Powell, Adeya; Gordon, Derrick; Kershaw, Trace (AIDS education and prevention : official publication of the International Society for AIDS Education, 2016)
Sexting, sending, or receiving sexually suggestive or explicit messages/photos/videos, have not been studied extensively. The aims of this study is to understand factors associated with sexting among minority (e.g., African- American, Hispanic) emerging adult males and the association between sexting and sexual risk. We recruited 119 emerging adult heterosexual males and assessed sexting and sexual risk behaviors. Fifty-four percent of participants sent a sext, and 70% received a sext. Participants were more likely to sext with casual partners than with steady partners. Multiple regression analyses showed that participants who sent sexts to steady partners had significantly more unprotected vaginal intercourse and oral sex. Participants who sent sexts to casual partners had significantly more partners, and participants who received sexts from casual partners had significantly more unprotected oral sex and sex while on substances. We found that sexting is a frequent and reciprocal behavior among emerging adults, and there were different patterns of significance for sexts with casual and steady partners.